Model‐Informed Development and Registration of a Once‐Daily Regimen of Extended‐Release Tofacitinib. Issue 6 (9th February 2017) - Lamba, M; Hutmacher, MM; Furst, DE; Dikranian, A; Dowty, ME; Conrado, D; Stock, T; Nduaka, C; Cook, J; Krishnaswami, S
Abstract : Extended‐release (XR) formulations enable less frequent dosing vs. conventional (e.g., immediate release (IR)) formulations. Regulatory registration of such formulations typically requires pharmacokinetic (PK) and clinical efficacy data. Here we illustrate a model‐informed, exposure–response (E‐R) approach to translate controlled trial data from one formulation to another without a phase III trial, using a tofacitinib case study. Tofacitinib is an oral Janus kinase (JAK) inhibitor for the treatment of rheumatoid arthritis (RA). E‐R analyses were conducted using validated clinical endpoints from phase II dose–response and nonclinical dose fractionation studies of the IR formulation. Consistent with the delay in clinical response dynamics relative to PK, average concentration was established as the relevant PK parameter for tofacitinib efficacy and supported pharmacodynamic similarity. These evaluations, alongside demonstrated equivalence in total systemic exposure between IR and XR formulations, provided the basis for the regulatory approval of tofacitinib XR once daily by the US Food and Drug Administration.